DOI: 10.11606/d.11.2007.tde-26102007-095441
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação e armazenamento de híbridos de milho verde visando à produção de pamonha

Abstract: Aos meus pais José AméricoJosé Américo José Américo José Américo e Azize Azize Azize Azize, exemplos de vida e luta, por estarem sempre presentes incentivando e apoiando a minha caminhada, dando-me muito AMOR, carinho e compreensão, pois sem a presença e esforço deles eu nada seria. Aos meus irmãos Rodrigo Rodrigo Rodrigo Rodrigo e Fábio Fábio Fábio Fábio, pelo carinho e incentivo. Ao meu namorado Ricardo Ricardo Ricardo Ricardo, que nos momentos finais esteve ao meu lado disposto a ajudar-me com paciência, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
3

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
3
1
3
Order By: Relevance
“…Nevertheless, the L* component values obtained in the present work were generally higher than those found in other studies on green corn (72.23 on the Hunter scale) (LEME, 2007). Higher L* values are expected for green corn compared to ripe corn, because the former is lighter in color.…”
Section: Colorcontrasting
confidence: 89%
See 2 more Smart Citations
“…Nevertheless, the L* component values obtained in the present work were generally higher than those found in other studies on green corn (72.23 on the Hunter scale) (LEME, 2007). Higher L* values are expected for green corn compared to ripe corn, because the former is lighter in color.…”
Section: Colorcontrasting
confidence: 89%
“…Protein content was 64% lower than the reference values reported by Taco (UNIVERSIDADE..., 2006), but similar between the treatments. In contrast, other studies on dried kernels showed that agroecological corn has higher protein content compared to the conventional corn (LEME, 2007). This parameter, however, is not of primary importance, because even corn varieties with high protein content lack lysine and tryptophan -two important essential aminoacids for human growth (PAES, 2008).…”
Section: Physicochemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Muitos estudos acerca da importância de diferentes modalidades sensoriais para a aceitabilidade do consumidor levam à conclusão de que o sabor é a modalidade mais importante, seguido pela textura e aparência. Tais conclusões não consideram o enorme esforço que as indústrias de alimentos emprega para desenvolver características de textura favoráveis e mantê-las durante a vida útil dos produtos (LEME, 2007).…”
Section: Textura De Produtos Enriquecidos Com Fibrasunclassified
“…A textura pode ser considerada uma manifestação das propriedades reológicas de um alimento e várias são as razões para se conhecer tais propriedades reológicas, dentre elas: a) efetuar o controle de qualidade de matériasprimas, de processos de fabricação e de produtos finais; b) estudar a influência de componentes de formulação e relacionar a estrutura dos produtos com as suas características reológicas; e c) correlacionar os dados reológicos com as avaliações organolépticas (LEME, 2007).…”
Section: Textura De Produtos Enriquecidos Com Fibrasunclassified